Conceptual Framework Of Intellectual Capital Influences To Corporate Efficiency - Ketut Rina Purnami Dewi; Nugroho Priyo Negoro; Yani Rahmawati (Institut Teknologi Sepuluh Nopember, 2018)
The emerging issue of labour piracy in Indonesia makes human resources become the most valuable assets. Labour piracy is mostly found in financial corporate to minimize cost, because there are limited capable employees available. The previous study found, the average Indonesian employee turnover in bank was 2-10 years. Approximately of 54% employees were willing to leave their job earlier and moved to others financial corporate with higher salary, and some others prefer to get a better career path, hence resigning the current job became the best decision for them. Training and education expense are increasing, but they have capability in minimizing corporate efficiency. Intellectual Capital (IC) played an important role in financial industry. This research aims to provide a conceptual framework of IC role to corporate efficiency. Study found that there is significant positive effect of IC to corporate efficiency. Study also revealed several factors of IC that influence the corporate efficiency.